7Y+11=17

Simple and best practice solution for 7Y+11=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7Y+11=17 equation:


Simplifying
7Y + 11 = 17

Reorder the terms:
11 + 7Y = 17

Solving
11 + 7Y = 17

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 7Y = 17 + -11

Combine like terms: 11 + -11 = 0
0 + 7Y = 17 + -11
7Y = 17 + -11

Combine like terms: 17 + -11 = 6
7Y = 6

Divide each side by '7'.
Y = 0.8571428571

Simplifying
Y = 0.8571428571

See similar equations:

| 1/2-x+7=3/4+2x | | 76=38(r) | | 4y+2y=5y+7 | | r+2.1=6.1 | | x+10+2x+7=9x+9 | | 3(5m-6)-28= | | (3/4)(2x+1)=2 | | 4+14s-2=7s+74-5s | | 11x-99=(x-9) | | u^3+27v^3=0 | | 3/4(2x+1)=2 | | 2/5(x-2)=-3 | | 35-3x=15x+15 | | 4x+2(x+6)=38 | | 7-9x=124-30x | | 7x-8=3-2x | | 5(z+7)= | | 118-4x=3x+20 | | -27x-3x=8-10x | | 1.1x-2.2+x-4.5= | | 6c+2c= | | 81u^4-1=0 | | -2a^2+30a=4a+60 | | x+4-2(x-1)=7 | | (k+5)x*2-10x+3=0 | | 7x+9=x+3 | | -11x-12=-12 | | 3x+1=x^2-2x+1 | | 15-3x=x-7 | | x(x-m)=12m^2 | | 3v^2-10v=8 | | -7y=x+56 |

Equations solver categories